Determination of sulfonamides in selected Malaysian swine wastewater by high-performance liquid chromatography - Malintan, N.T.; Mohd, M.A. (2006)
An analytical HPLC method for the simultaneous determination of eight sulfonamides in swine wastewater was developed. The samples were collected from three states in Malaysia. Sample clean up was carried out by employing solid-phase extraction using a 60 mg Oasis HLB (Waters) cartridge with 3 ml reservoir. The HPLC column used was Supelcosil C18 (250 mm x 4.6 mm I.D.) and elution was carried out using gradient mode. The mobile phases used were acetonitrile and 0.5 acetic acid in purified water. Antibiotics were detected using UV absorbance at 272 nm. Recoveries obtained for sulphanilamide ranged from 31.9 +/- 5.1 to 36.2 +/- 1.0, while recoveries for other sulfa drugs studied were from 91.9 +/- 5.0 to 106.0 +/- 1.1. The limit of quantitation (LOQ) for sulfamerazine, sulfamethazine and sulfamethoxypyridazine was 7.5 ng/L, while the LOQ for the other studied antibiotics was 5.0 ng/L. The method was used to analyse sulfonamides in wastewater collected from selected Malaysian swine facilities. (c) 2006 Elsevier B.V. All rights reserved.